Do service sector trends stimulate entrepreneurship? A socio-economic labour market perspective. (18th July 2008) - Bogenhold, Dieter; Fachinger, Uwe
The aim of this paper is to discuss the service sector trends in relation to the issue of entrepreneurship. Talking about entrepreneurship in service industries means talking about a variety of items and related academic fields. The paper tries to concentrate on one specific thematic area by taking a labour market perspective and by combining changes in the division of work and occupations with the division of firms and related dynamics in the firm population. The results of discussion can be summarised: very much of the revival of entrepreneurship goes hand in hand with the broader service sector trend and within the new service sector domain, not always spectacular new firms with dynamics towards growth and job creation exist but also those which are small and remain small as micro firms. Finally, the emerging service sector trend coincides with the trend towards a so-called knowledge economy and a revival of new self-employed independent knowledge-workers.